A Study of How the Velocity of Detonation Affects Fragmentation and the Quality of Fragments in a Muckpile (The Australasian Institute of Mining and Metallurgy, 1995)
Blasting in Norwegian mines is often carried out by contractors who tend to look for the cheapest solution, without concern about fragment quality. The requirementsfor a contractor are usually only related to the maximum size of boulders and the quantity per month. Even when the owners of the mine are responsible for blasting, very little effort is made to optimise the blasting process. This paper presents test methods which were used and results from small-scale and full-scale blasting tests. In the small-scale tests, cubes 500 x 500 x 500 mm of four different rock types were blasted in a chamber, using two types of dynamite explosive. The velocity of detonation (VOD) for the dynamite explosives was 3000 m/s and 6000 m/s respectively. Three cubes of each rock type were blasted with each type of explosive, and a total of six cubes of each rock type was used. The entire muckpile (approximately 350 kg) was- sieved and weighed after each blast and fragments between 8-16 mm were tested for impact values and flakiness. The results of these tests clearly showed improvement in fragmentation the closer the acoustic impedance ratio of the explosive (VOD x density) over the rock (Cp density) was equal to one. The results also showed that the quality of the fragments (in terms of impact values) tends to be better when the cubes are blasted with the high velocity dynamite.